Shallow-Water Coral Communities Support the Separation of Marine Ecoregions on the West-Central Florida Gulf Coast - Walker, Brian K.; Eagan, Shelby; Ames, Cory; Brooke, Sandra; Keenan, Sean; Baumstark, Renè (Frontiers in Ecology and Evolution, 2020)
Florida’s west coast is a 170,000 km2 bedrock shelf (WFS) comprised of north-south discontinuous carbonate outcroppings extending more than 200 km from the intertidal zone to a depth of 200 m. These outcrops support diverse benthic communities, which contribute to a multi-billion dollar recreational and commercial fishing industry, yet only about 5% of their extent has been studied in detail. Benthic communities shift over a 6.5° geographic range, but the locations of these shifts are not well-defined. Previous studies have suggested a break in biogeographic regions at Tampa Bay, south at Cape Romano, and north at Cedar Key. The goal of this study was to map and investigate the shallow WFS marine hardbottom north and south of Tampa Bay, FL to identify differences in benthic communities and identify ecoregion boundaries. Habitat mapping yielded 295.89 km² of hardbottom which differed in extent between Sarasota and Pasco counties. Benthic surveys tabulated 4,079 stony coral colonies of nine species and 1,918 soft corals. Stony corals were dominated by Siderastrea radians, Oculina robusta, Solenastrea hyades, and Cladacora arbuscula less than 10 cm in diameter. Distinct differences in these communities were evident from south to north. The main community shift indicated an ecoregion boundary at, or very near, the mouth of Tampa Bay. Another shift associated with the Bahamas Fracture Zone (BFZ) occurred at the Pinellas and Pasco county border. The outputs of this work provide the first detailed benthic habitat map of the area, a detailed survey of the composition of hardbottom benthic communities in the region, identify Tampa Bay as a coastal benthic biogeographic transition, and illustrate the influence of the BFZ on coastal communities. These findings illustrate a need for additional WFS benthic research and mapping to give a more comprehensive understanding of coral community biogeography in the context of future warming conditions and the potential tropicalization. Unifying seafloor mapping data, mapping new areas with high probability of hardbottom resources, and collecting benthic community data over broader scales will refine community biogeographic zonation. This is a necessary precursor to any long-term community monitoring to detect spatial shifts in communities and population modeling.